2017
DOI: 10.1038/s41598-017-14385-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial genomic DNA from used Xpert MTB/RIF cartridges can be utilised for accurate second-line genotypic drug susceptibility testing and spoligotyping

Abstract: Xpert MTB/RIF (Xpert) is a widely-used test for tuberculosis (TB) and rifampicin-resistance. Second-line drug susceptibility testing (DST), which is recommended by policymakers, typically requires additional specimen collection that delays effective treatment initiation. We examined whether cartridge extract (CE) from used Xpert TB-positive cartridges was, without downstream DNA extraction or purification, suitable for both genotypic DST (MTBDRplus, MTBDRsl), which may permit patients to rapidly receive a XDR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, the cartridges had to be punctured with a syringe to extract DNA. 22,23 A strength of this TB-Diskebased workflow is that, besides providing DNA for TB testing, a separate external reaction tube containing DNA for additional tests provides maximal flexibility; and no puncturing of the cartridge is required. After diagnosis of TB, Inh, Rif, and SLD resistance markers can be immediately investigated by PCR, LPA, or potentially targeted next-generation sequencing in a stepwise algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cartridges had to be punctured with a syringe to extract DNA. 22,23 A strength of this TB-Diskebased workflow is that, besides providing DNA for TB testing, a separate external reaction tube containing DNA for additional tests provides maximal flexibility; and no puncturing of the cartridge is required. After diagnosis of TB, Inh, Rif, and SLD resistance markers can be immediately investigated by PCR, LPA, or potentially targeted next-generation sequencing in a stepwise algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on a hemi-nested real-time polymerase-chain-reaction (PCR) assay to amplify an Mtb-specific sequence of the rpoB gene. The turnaround time of this assay is short (2–3 h), and the problem of cross-contamination is eliminated because of self-contained cartridges [ 30 ]. It uses three specific primers and five unique molecular probes to ensure a high degree of specificity, and NTM does not confound testing [ 31 ].…”
Section: Mtb Diagnosismentioning
confidence: 99%
“…dCEs were extracted from all positive cartridges by puncturing the rear chamber with a sterile 29 G × 1/2′′ 1 ml insulin syringe (Avacare, South Africa) ( Fig. 2A,B) as described previously 6 . The full volume was extracted (~15 µl for Xpert; ~35 µl for Ultra).…”
Section: Ultra and Xpert On Dilution Series Of Mycobacterium Tuberculmentioning
confidence: 99%
“…Previous work showed that mycobacterial genomic DNA can be recovered from the rear diamond-shaped chamber of used Xpert MTB/RIF (Xpert) cartridges after the test is complete. This diamond cartridge extract (dCE) is useful for downstream testing with the MTBDRsl line probe assay (LPA) (Hain Lifescience, Germany), the only World Health Organization (WHO)-endorsed molecular test for second-line drug resistance, and spoligotyping 6 , a method useful for monitoring the molecular epidemiology of TB outbreaks. This additional testing does not require extra specimen collection nor additional downstream DNA extraction, both of which can exacerbate patient loss within the diagnostic care cascade.…”
mentioning
confidence: 99%